La capacidad disuasiva israelí y la guerra de Líbano de 2006 - Mesa Delmonte, Luis (Revista Mexicana de Política Exterior, 2022)
Israel’s highly trained and bellicose military apparatus, armed with advanced intelligence and state-of-the-art technology, both American-and Israeli-made, has traditionally served as an effective war deterrent in the region, particularly in light of its numerous military victories over the decades. Nonetheless, the author of this article believes Israel’s military potential and its power to deter symmetrical armed conflicts has been called into question in recent years. This is especially true in the case of asymmetric warfare, which has forced Israel to rethink not only its combat strategies and methods, but its thought processes and policies in general. Mesa Delmonte mentions some of these new asymmetrical threats, such as the Palestinian uprisings, suicide “martyrological” bombings and the firing of primitive Qassam missiles, as a prelude to a more in-depth analysis of the war with Lebanon that broke out in the summer of 2006. Some of the factors that explain the highly developed asymmetric warfare capacity demonstrated by Hezbollah in this confrontation are discussed, along with the strategy employed by the Israeli Defense Forces and the errors that thwarted Israel’s attempt to decapitate and destroy this Lebanon-based Shi’a Islamic political and paramilitary group. The author picks up on the threads of Israel’s internal debate vis-à-vis the need to reinstate its dissuasive power, and discusses its attacks on Gaza and Syria. In Mesa Delmonte’s view, beyond these new asymmetrical threats and Israel’s pressing need to revert its “accumulated dissuasive deficit”, emphasis must be placed on a negotiated solution to the Arab-Israeli conflict, overturning traditional views that only force and a military balance can bring about peace in the region.